Withdrawal from mental and psychosocial care during pregnancy. (December 2014) - Quispel, Chantal; Lambregtse-van den Berg, Mijke; Kaan, Marjolein; van den Berg, P. Mirelle; Hoogendijk, Witte J. G.; Steegers, Eric A. P.; Koudstaal, Thamar; Muis, Inge; Bonsel, Gouke J.
Abstract Psychopathology, psychosocial problems and substance use (PPS) commonly occur in pregnant women, and can have a negative impact on the course of pregnancy and the healthy development of the child. As PPS often remains undetected and untreated during pregnancy, we developed and implemented a four-step screen-and-treat protocol in routine obstetric care, with: (i) screening including triage and subsequent confirmation, (ii) indication assessment, (iii) transfer towards care and (iv) utilization of care. Adherence to the protocol and risk factors associated with dropout were examined for 236 Dutch pregnant women in a deprived urban area. Seventy-nine percent of women accepted the screening, 21% dropped out during triage, 15% during confirmation, 3% during transfer and 8% thereafter. Provided reasons for dropout were lack of time and lack of perceived benefit. In particular, smokers, multiparous women, and women of non-Western ethnicity dropout on the way towards mental and psychosocial care. For a successful implementation of the protocol in the future, with improved adherence of pregnant women to the protocol, education of women on PPS risks, motivational skills and compulsory treatment are worth investigation.